Insolvency trends and the economy before the outbreak of the pandemic - Fuchsbichler, Richard; Kouba, Luděk (Momentum Quarterly, 2024)
In the years leading up to the outbreak of the COVID-19 pandemic in the spring of 2020, both in Austria and internationally, a continuous decline in corporate insolvencies could be observed across different economic phases. This empirical development seems to contradict the previous theoretical assumption of an anticyclical response of insolvency figures to cyclical impulses. This raises the question of whether the development of insolvencies had already decoupled from economic growth before the outbreak of the pandemic and whether alternative factors such as the low interest rate policy or the emergence of "zombie companies" have a decisive influence. Using time-series analysis methods, we find no empirical evidence of a decoupling of insolvencies and insolvency contingency development for Austria until the outbreak of the pandemic. Insolvency contingency cases and payments continue to react anticyclically, i.e. they tend to fall during economic upturns and rise during economic downturns.
Keywords: insolvency; insolvency contingency fund; economic growth; regression- and correlation analysis; Austria